Research on influence of new structural design regulations on general design of steel towers. Issue 1 (1st November 2022) - Fang, Zhenggang; Li, Zheng; Li, Yigang; Liu, Rui
Abstract : This work describes the main revision content of the power industry standard (DL/T 5486-2020) (Technical specification for the design of steel supporting structures of overhead transmission line). And the effects of the new revision standard (DL/T 5154-2012) Technical code for the design of tower and pole structures of overhead transmission line (DL/T 5154-2012), on the general design of 35kV~750kV steel towers are analyzed in depth. Subsequently, the optimization suggestions of general design of the steel tower are proposed.